2009
DOI: 10.1111/j.1749-6632.2009.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α Antagonist Survival Rate in a Cohort of Rheumatoid Arthritis Patients Observed under Conditions of Standard Clinical Practice

Abstract: A cohort of rheumatoid arthritis (RA) patients in the Lombardy Rheumatology Network (LOHREN) registry and receiving anti-TNF therapy was evaluated after 6, 12, 24, and 36 months. Of the 1114 patients in the registry 1064 met the clinical criteria for inclusion with 519 receiving infliximab, 303 adalimumab, and 242 etanercept. The therapeutic survival curve of these patients showed that the likelihood of continuing anti-TNF therapy was 78.8% after 12 months, 65.2% after 24 months, and 52.9% after 36 months, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 28 publications
(40 reference statements)
10
64
1
5
Order By: Relevance
“…Several causes can justify switching between Table 4 Clinical and laboratory characteristics of the groups with low and moderate/high disease activity, according to fi nal DAS28, after switching between anti-TNF-alpha agents anti-TNF-alpha agents of the same class or with a similar mechanism of action; however, usually the failure in responding (PF or SF) and the AEs are the major causes in most clinical studies published. 1,2 Similarly to the present study, Marchesoni et al, 13 in a large cohort of patients on anti-TNF-alpha therapy, have reported that of the 1,064 individuals assessed, 38.1% discontinued the medication. Of those, 44.4% discontinued due to ineffi cacy, 47.9% due to AEs, and 2.5% due to disease remission.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several causes can justify switching between Table 4 Clinical and laboratory characteristics of the groups with low and moderate/high disease activity, according to fi nal DAS28, after switching between anti-TNF-alpha agents anti-TNF-alpha agents of the same class or with a similar mechanism of action; however, usually the failure in responding (PF or SF) and the AEs are the major causes in most clinical studies published. 1,2 Similarly to the present study, Marchesoni et al, 13 in a large cohort of patients on anti-TNF-alpha therapy, have reported that of the 1,064 individuals assessed, 38.1% discontinued the medication. Of those, 44.4% discontinued due to ineffi cacy, 47.9% due to AEs, and 2.5% due to disease remission.…”
Section: Discussionsupporting
confidence: 82%
“…The greatest risk of discontinuing therapy due to some AE was associated with advanced age and current use of GC; while the loss of effi cacy was associated with previous use of more than three DMARDs and higher ESR. 13 In 40.5% of our patients, the reason for switching the anti-TNF-alpha agent was the presence of an AE. Usually, high retention rate of the second anti-TNF-alpha agent is observed in the fi rst year (50%-70%), and switching from one anti-TNFalpha agent to another can elicit an adequate clinical response, especially if caused by toxicity, as shown in a recent systematic review that assessed approximately six thousand patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Two of the studies analyzed rates of switching between TNF blockers [10,11], and others focused on treatment persistence [12][13][14][15][16][17][18][19]. None of the studies analyzed rates of restarting the index TNF blocker after a treatment gap.…”
mentioning
confidence: 99%
“…165 These disorders are often associated with an increased risk of cardiovascular comorbidities, and the benefits of TNF-α inhibition, apart from anti-inflammatory efficacy and improved survival, 166 are thought to include cardiovascular protection. Consequently, many studies have been conducted to investigate the vascular effects of TNF-α inhibition in these patients, and they have produced an abundance of controversial results.…”
Section: Tnf-α Antagonism In Autoimmune Diseasesmentioning
confidence: 99%